ICTs in Latin America: An overview - Santos, Rodrigo Martin (2009)
In this paper, the state-of-the-art on the field of Information and Communications Technologies (ICTs) in Latin America is presented. Its main contribution consists in the localization of common objectives for the majority of the countries in the region. Although the countries are very heterogeneous from the cultural and geographical perspectives, there are many common factors that can be exploited in order to develop their economies. At first sight, Brazil or Mexico with their huge populations and big economies are giants compared to other countries like Bolivia or Costa Rica. However there are many common problems in all of them that can be addressed with a common strategy. An important question that this presentation tries to answer is the ICT profile of Latin America: consumer or producer. Data from the World Bank on ICT infrastructure and from the academic sector on the actual situation of the R&D activities in the region are analyzed to answer this question.